Adherence to a flexible extended regimen for oral hormonal contraception provided in a blister packaging compared with an adherence-supporting digital tablet dispenser: historical comparison of data from two clinical studies - Elliesen J; Trummer D (Dove Medical Press, 2016)
Jörg Elliesen, Dietmar Trummer Bayer Pharma AG, Berlin, Germany Background: The Clyk™ digital pill dispenser helps ensure correct and consistent administration of a flexible extended regimen of the combined oral contraceptive, ethinylestradiol (EE) 20 µg/drospirenone 3 mg (EE/drospirenoneFlex; YAZ® Flex), guiding users through the intake cycle and 4-day pill break and providing visible and acoustic daily reminders when pill intake is due. A study showed that the audible alarm function of the dispenser could help reduce the number of missed pills, but it lacked an appropriate “non-dispenser” group for a meaningful assessment of the impact of the dispenser on adherence. This study indirectly assessed the overall effect of the digital dispenser on adherence by comparing data from a treatment with standard blister packaging.Materials and methods: One-year adherence data were compared from two similarly designed, Phase III, open-label, randomized trials of EE/drospirenoneFlex. In study 1, women used diary cards to record adherence with EE/drospirenoneFlex dispensed in blister packs (n=640), and in study 2 the dispenser was used with the alarm activated (n=250) or deactivated (n=248) in addition to using diary cards.Results: A mean (±SD) of 4.3 (±4.24) missed pills over 1 year were recorded in diary cards among women who dispensed their pills from the blister packages (study 1) compared with 1.0 (±2.4) recorded by the alarm-activated dispenser (study 2). In study 2, a mean of 1.9 (±4.2) missed pills were reported in the diaries over 1 year compared with 4.4 (±9.1) from automatic recording by the dispenser (both arms of study 2), indicating underreporting of missed pills in diary cards vs the digital dispenser. Adjusting for this rate of underreporting, an estimated mean of ten pills were missed over 1 year by women using EE/drospirenoneFlex in blister packs, or ten times more than with the digital dispenser with activated acoustic alarm.Conclusion: The digital dispenser helps reduce the number of missed pills and increases adherence. Keywords: compliance, contraception, drospirenone, ethinylestradiol, flexible extended regimen, efficacy, pill dispenser